Analisis Perbandingan Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Cinema XXI Dan CGV - Agustinus Sijabat, Yehezkiel Zona; Iskandar, Donant Alananto (STREAMING, 2024)
The purpose of this study aims to investigate and compare prices and service quality on customer satisfaction of XXI Cinemas and CGV Cinemas in the DKI Jakarta province. This study uses a quantitative approach with a survey method by collecting data using a questionnaire distributed to consumers of XXI Cinemas and CGV Cinemas in the DKI Jakarta province. The research sample consisted of 60 respondents to Cinema XXI and 60 respondents to Cinema CGV. The results of this study indicate that the better the service quality, the more satisfied consumers will be. The results of this study can be a reference for companies that manage XXI Cinemas and CGV Cinemas to continuously improve service quality and apply prices according to the benefits that consumers get. This is expected to increase consumer satisfaction in both cinemas.